Effects of digital marketing data analytics and traditional marketing data analytics on a new product success: a study of SQUARE Toiletries Limited - Salam, Tahmim (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.